Principal Leadership in Changing Teacher Performance at SMA Negeri 1 Donggo - Maryanton, Maryanton; Umar, Umar; Pertiwi, Yulia Resha (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is descriptive with a qualitative approach. This study uses observations, interviews, and documentation as data sources. Teachers and school administrators are the respondents in this survey. Coding, organization, and checks are used in data analysis. Meanwhile, diligence, triangulation, and thorough descriptions are used to ensure the results of the research. The purpose of this study is to find out how much and how well instructors work in fulfilling the assigned obligations and realizing their performance in accordance with the standards required by professional principals. The findings of the study show that: first, the principal of SMA Negeri 1 Donggo has used a leadership strategy that is quite good to improve teacher performance. However, there are still a number of areas that need to be improved to foster work discipline, foster positive attitudes and mentalities, and provide incentive allowances to teachers. This is evident from a number of sources, especially teacher performance. Second, problems with the principal's ability to influence teacher performance at SMA Negeri 1 Donggo, inadequate work ethic and low community involvement. Third, how the principal's actions have affected the performance of the instructors at SMA Negeri 1 Donggo, the environment at work, the reward for an honest and reliable approach. This cannot be separated from the planning of teacher performance change activities, the implementation of teacher performance change activities, directing teacher performance change activities, and evaluating teacher performance change activities.